Synthesis and Toxicity Test Of Zinc (II) Pyridine-2,6-Dicarboxylate Complexes - Fahimah Martak; Tia Ayu Christanti (IPTEK The Journal for Technology and Science, 2014)
Complexes of zinc (II) with pyridine-2,6-dicarboxylic acid were synthesized from a reaction between zinc(II) chloride and pyridine-2,6-dicarboxylic acid with two different methods. The first method was carried out by reflux method, mixing a certain mole ratio of metal and ligand in the mixed solution of methanol:water (1:1) as the solvent. The second method was carried out by employing a direct reaction of metal and ligand in a 1:2 mole ratio of the same solvent as it is of the first method. The first method yielded a small clear crystal grains shaped like parallelogram with the molecular formula of [Zn(H2dipic,dipic)Zn2(10H2O)]Cl4∙5H2O (Complex I-trinuclear). The second method yielded the colorless needle-like crystals and molecular formula [Zn(H2dipic)2Zn(H2O)5]Cl4∙2H2O (Complex II-dinuclear). Both complex compounds were tested their toxicity using Brine Shrimp Lethality Test (BSLT) method and obtained LC50 values of 989.26 and 503.32 ppm, respectively.